MATHEMATICAL COMMUNICATION ABILITY OF CLASS V SD STUDENTS ON FLAT BUILDING MATERIALS VIEWED FROM GENDER - Kurnia Islami; Rien Anitra; Sumarli Sumarli (PROGRES PENDIDIKAN, 2023)
This study aims to describe the mathematical communication abilities of fifth grade students on the material of flat shapes in terms of the gender of students at SDN 84 Singkawang. The research used is descriptive quantitative research. The population of this study was the fifth grade students at SDN 84 Singkawang consisting of VA and VB classes, which consisted of 44 students. The data collection technique used was the test technique and the data analysis technique used was quantitative descriptive analysis with percentages. The results showed that mathematical communication skills in terms of gender where the mathematical communication skills of fifth grade male students in solving problems, subjects with high abilities were able to fulfill all indicators of students' mathematical communication abilities. Subjects with moderate ability are less able to explain ideas, everyday situations and mathematical relationships in writing with pictures. While the mathematical communication abilities of fifth grade female students in solving questions on subjects with high abilities were able to fulfill all indicators of students' mathematical communication abilities. Subjects with moderate ability are less able to explain ideas, everyday situations and mathematical relationships in writing with pictures. Meanwhile, subjects with low abilities are less able to explain ideas, everyday situations and mathematical relations in writing with pictures and communicate the conclusions of answers to problems according to the results of the questions. Thus it can be concluded that students' mathematical communication abilities in terms of gender in this study averaged 74% in the moderate category.